Reading and Learning Difficulties in English Language Among Private and Public Primary School Pupils in the Federal Capital Territory (FCT), Nigeria - Adebayo, Odeniyi Olujinmi; Marian, Folorunsho Gbemisola (European Scientific Journal, ESJ, 2017)
The importance of education has often been underscored by scholars and researchers across different disciplines. Primary education is very crucial to the development of any nation. This is because of the liberating role it plays within the society. Studies have shown that when a person undergoes primary education, many problems that may constitute potential threats to the national and global well-being of a nation are solved. These problems include ignorance, illiteracy, religious violence, insecurity, and political servitude. This study investigated the reading and learning difficulties in English language among private and public primary school pupils in the Federal Capital Territory (FCT) in Nigeria. Descriptive survey research design was adopted for this study. The populations for this study are pupils of private and public primary schools in the Federal Capital Territory. It constitutes 491 primary schools in Abuja and an enrolment figure of 185,808. The study adopts multistage sampling technique which is a probability sampling technique. Data was analysed using simple percentages, frequency counts, and tables. Findings showed that primary school pupils experience some difficulties in reading and learning English language which is the medium of instruction in their schools. Some of these problems are environment induced, while others are foundational. In conclusion, the study recommends that parents must ensure they devote adequate time to help their wards develop the interest and confidence needed to achieve comprehension. Teachers need to be more strategic in the teaching of English language, especially by encouraging listening to the language first and constant practice.